2019
DOI: 10.1037/adb0000455
|View full text |Cite
|
Sign up to set email alerts
|

Do misperceptions of peer drinking influence personal drinking behavior? Results from a complete social network of first-year college students.

Abstract: This study considered the influence of misperceptions of typical versus self-identified important peers’ heavy drinking on personal heavy drinking intentions and frequency utilizing data from a complete social network of college students. The study sample included data from 1,313 students (44% male, 57% White, 15% Hispanic/Latinx) collected during the fall and spring semesters of their freshman year. Students provided perceived heavy drinking frequency for a typical student peer and up to 10 identified importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 28 publications
2
29
1
2
Order By: Relevance
“…Social norms theory (Berkowitz, 2004) acknowledges that perceptions of others' behaviors are often inaccurate, which is particularly problematic given that college students tend to overestimate their peers' alcohol use (Cox et al, 2019;Perkins et al, 2015). Accordingly, norms-based interventions such as personalized normative feedback (PNF) have been designed to correct over-inflated normative perceptions, which can subsequently reduce students' alcohol use (Dotson et al, 2015;Neighbors et al, 2018;Patrick et al, 2014).…”
mentioning
confidence: 99%
“…Social norms theory (Berkowitz, 2004) acknowledges that perceptions of others' behaviors are often inaccurate, which is particularly problematic given that college students tend to overestimate their peers' alcohol use (Cox et al, 2019;Perkins et al, 2015). Accordingly, norms-based interventions such as personalized normative feedback (PNF) have been designed to correct over-inflated normative perceptions, which can subsequently reduce students' alcohol use (Dotson et al, 2015;Neighbors et al, 2018;Patrick et al, 2014).…”
mentioning
confidence: 99%
“…Thus, it is possible that reports of dating partners' drinking are subject to distortion. However, it is important to note that perceptions that others are heavy drinkers is associated with adolescents' heavy use (Cox et al, 2019). Additionally, the initial analyses indicated that daters compared with non-daters reported higher frequency of drinking.…”
Section: Discussionmentioning
confidence: 97%
“…For example, adolescents' initial substance use is associated with an increase in the number of friends who are substance users over time reflecting a selection effect; and the initial number of friends who use substances is associated with increases in substance use reflecting a modeling effect (Simons-Morton & Chen, 2006). Importantly, although young people have tended to overestimate heavy drinking among their peers, nevertheless, such perceptions are associated with more frequent heavy drinking (Cox et al, 2019).…”
Section: Peer Influencementioning
confidence: 99%
“…Young adults tend to overestimate the amount and frequency of drinking among their peers which is then related to their own decisions about how often and how much to drink. Those who perceive higher rates of consumption among their peers drink more (Cox et al, 2019;Neighbors, Lee, Lewis, Fossos, & Larimer, 2007). Young adults also overestimate what their peers would deem to be acceptable alcohol consumption.…”
Section: College Student Alcohol Usementioning
confidence: 99%